2017
DOI: 10.1242/dev.146894
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Btbd7 is essential for region-specific epithelial cell dynamics and branching morphogenesis in vivo

Abstract: Branching morphogenesis of developing organs requires coordinated but poorly understood changes in epithelial cell-cell adhesion and cell motility. We report that Btbd7 is a crucial regulator of branching morphogenesis in vivo. Btbd7 levels are elevated in peripheral cells of branching epithelial end buds, where it enhances cell motility and cellcell adhesion dynamics. Genetic ablation of Btbd7 in mice disrupts branching morphogenesis of salivary gland, lung and kidney. Btbd7 knockout results in more tightly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Figure 4A shows morphologies for increasing values of T . Consistent with the inhibition or knockout of Btbd7 [48,6] at low values of T the tissue did not branch, because only few random cell protrusions were strong enough to overcome the effect of the chemoinhibitor. For slightly higher cell motility, at cellular temperatures of around T = 20, the tissue developed droplet-like extensions: as soon as one or a few protrusions locally overcame the effect of the inhibitor the curvature locally increased leading to reduced levels of chemoinhibition.…”
Section: Random Motility Regulates Branch Initiation and Branching Speedmentioning
confidence: 79%
See 1 more Smart Citation
“…Figure 4A shows morphologies for increasing values of T . Consistent with the inhibition or knockout of Btbd7 [48,6] at low values of T the tissue did not branch, because only few random cell protrusions were strong enough to overcome the effect of the chemoinhibitor. For slightly higher cell motility, at cellular temperatures of around T = 20, the tissue developed droplet-like extensions: as soon as one or a few protrusions locally overcame the effect of the inhibitor the curvature locally increased leading to reduced levels of chemoinhibition.…”
Section: Random Motility Regulates Branch Initiation and Branching Speedmentioning
confidence: 79%
“…The previous section showed that the proposed branching mechanism is driven by random cell motility. Interestingly, Btbd7, a positive regulator of epithelial cell motility, is required for branching morphogenesis of salivary glands and the lung [48], and is expressed in branching end buds in a variety of branching epithelial organs [6]. Knock-out of Btbd7 reduces epithelial cell motility in the end buds of submandibular salivary glands, leading to incomplete branching [6].…”
Section: Random Motility Regulates Branch Initiation and Branching Speedmentioning
confidence: 99%
“…The previous section showed that the proposed branching mechanism is driven by random cell motility. Interestingly, Btbd7, a positive regulator of epithelial cell motility, is required for branching morphogenesis of salivary glands and the lung [46], and is expressed in branching end buds in a variety of branching epithelial organs [47]. Knock-out of Btbd7 reduces epithelial cell motility in the end buds of submandibular salivary glands, leading to incomplete branching [47].…”
Section: (D) Random Motility Regulates Branch Initiation and Branchinmentioning
confidence: 99%
“…Using techniques, such as particle image velocimetry (PIV) and vector mapping, his group investigated the modes of movement of different cells in 3D matrices. Their more recent work has focused on the role of BTBD7 in regulating adhesion and motility during morphogenesis in epithelial cells (Daley et al, 2017).…”
Section: Cell Migrationmentioning
confidence: 99%